OVERVIEW OF FACTORS CAUSING LONG LABOR IN PMB MASSIANA, SINTANG REGENCY - Yunida Haryanti; Lea Masan; Rizki Amartani; Yolanda Montessori; Paskalia Tri Kurniati (CV. Adiba Aisha Amira, 2025)
Background: World Health Organization (WHO) data shows that around 80% of maternal deaths are due to increasing complications during pregnancy, childbirth and after childbirth. The causes of maternal death are bleeding at 30.1%, hypertension at 26.9%, infection at 5.6%, abortion at 1.6%, prolonged labor at 1.8% and others at 34.5%. Data obtained from PMB Massiana shows that the incidence of prolonged labor in 2024 was 47 cases. Objective: To find out the description of the factors causing prolonged labor in PMB Massiana, Sintang Regency in 2024. Research Method: Descriptive quantitative with a retrospective approach, the sampling technique is total sampling, data collection using secondary data from medical record data, the research instrument is a check-list sheet. Research Results: Prolonged labor caused by power is caused by incoordination of uterine muscle contractions as many as 25 people (53%), then prolonged labor is caused by Passage due to abnormalities in the soft birth canal as many as 5 people (11%), and prolonged labor is caused by Passanger due to abnormalities in the shape and size of the fetus as many as 6 people (13%). Suggestion: Health services at PMB Massiana, Sintang Regency are quite good, but it is hoped that health workers will maintain existing services and even improve them. The services that must be improved are the provision of health education to mothers in labor about prolonged labor.